The economics of medical technology - Bolin, Kristian; Kaestner, Robert (Emerald, 2012)
Medical technology broadly defined to include all aspects of the process of treating disease (e.g., pharmaceuticals, medical devices, and surgical procedures) is profoundly important for individual health and, consequently, also for general welfare. Advances in medical technology convey the prospect of both improved population health and increased general welfare. However, because of the extensive regulation of the markets for healthcare goods and services, the development and application of medical technologies differs fundamentally from non-medical technological advances. In this volume of the Advances in Health Economics and Health Services Research series we present several papers that provide theoretical and empirical evidence about the market for medical technology.
Keywords: Medical -- Allied Health Services -- Medical Technology.; Business & Economics -- Public Finance.; Medical -- Pharmacology.; Health economics.; Health systems & services.; Medical technology -- Economic aspects.; elektronické knihy; electronic books